Influence of low-frequency fields on the process of yeast-containing wastewater treatment - Poshtarenko, Anna; Reshetnyak, Lyudmila (Problems of Environmental Biotechnology, 2021)
The study was aimed at investigating the effect of low-frequency radiation on the number of microorganisms, selection of the optimal mode (combination of voltage and exposure) of yeast-containing wastewater treatment in order to achieve maximum efficiency. The results of this study show that an increase in voltage and exposure to low-frequency radiation leads to a decrease in the total microbial count in yeast-containing wastewater.